2017
DOI: 10.18203/2394-6040.ijcmph20175085
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the mother-to-child transmission of HIV: findings from an early infant diagnosis program in Delta state Nigeria

Abstract: Background: Mother-to-child transmission (MTCT) of HIV has been a global issue being addressed with prevention of mother to child transmission (PMTCT) strategy. Nigeria is said to be responsible for 30% of the global burden of MTCT of HIV. Hence, Delta state of Nigeria had implemented its own PMTCT in line with the global plan to eliminate MTCT. This paper evaluates the determinants and level of effectives of PMTCT with a view to develop a framework to review the program in Delta state.Methods: This was a narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This finding is similar to the report by Dakum et al [51]; however, the proportion of DBS sample obtained at 6 -8 weeks in our study is twice as high as reported by Dakum et al [51] and Itiola et al [45] in the country. Reports on fairly large number of HIV-exposed infants in the country by Anoje et al, [28] Olerigbe et al, [41] Ibobo et al, [48] did not report 6 -8 weeks age of DBS sample collection. Higher DBS collection rates at 6 -8 weeks of 67.3%, 50%, and 79% have been reported in Ethiopia, [53] Malawi, [54] and Kenya, [55] respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding is similar to the report by Dakum et al [51]; however, the proportion of DBS sample obtained at 6 -8 weeks in our study is twice as high as reported by Dakum et al [51] and Itiola et al [45] in the country. Reports on fairly large number of HIV-exposed infants in the country by Anoje et al, [28] Olerigbe et al, [41] Ibobo et al, [48] did not report 6 -8 weeks age of DBS sample collection. Higher DBS collection rates at 6 -8 weeks of 67.3%, 50%, and 79% have been reported in Ethiopia, [53] Malawi, [54] and Kenya, [55] respectively.…”
Section: Discussionmentioning
confidence: 95%
“…[25] Transitioning to more efficacious cART for PMTCT between 2010 and 2012, several studies [26]- [42] in the country reported MTCT rates of between 0% [43] [44] and 9.7% [45]. Most recent reports from Sokoto, [46] FCT/Nasarawa state, [47] Delta, [48] Rivers [49] and Imo state [50] showed MTCT rates of 0.9%, 1%, 4%, 1.1%, and 3.7% respectively. A very large subregional report of EID of HEI by Dakum et al [51] reported a MTCT rate of 5.2% at 12 weeks postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 approximately 370,000 children became infected with HIV globally and most of these infections occurred through MTCT 15 . It is acknowledged that Nigeria accounts for 30% of the burden of MTCT of HIV in the world 14,16 . This justifies why Nigeria is one of the 22 focus countries of the Global Plan to Eliminate MTCT 1,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this research seeks to examine an EID program in Delta State of Nigeria with a view to determine the level of reduction of MTCT of HIV. A narrative literature review has previously been performed as background to this work 16 . Another study has also examined EID program in two other Southern States of Nigeria 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation